PERANCANGAN APLIKASI MODUL INTERAKTIF BERBASIS ANDROID PADA MATA PELAJARAN PEMROGRAMAN DASAR KELAS X TKJ DI SMK NEGERI 6 PADANG - Irsyadunas Irsyadunas; Ade Pratama; Lourena Mutiara Rilda (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
An interactive module is a learning tool or tool in which material, methods and evaluations are made in a systematic and structured manner in an effort to achieve the expected competency goals. The design of an Android-based interactive module application aims to provide a variety of learning processes in basic programming subjects in class X TKJ SMK Negeri 6 Padang. This system is an application program that can be accessed online at the android application store, which provides complete learning needs for students neatly packaged in an application in the form of providing material, competencies, evaluations to learning videos. In addition, from this study, several conclusions were obtained, namely (1) The application of an interactive module based on Android in class X makes it easy for students to do learning wherever and whenever, (2) makes it easy for teachers to present assignments and learning material, (3 ) With the application of interactive module applications in the learning process will increase student interest in learning.